Accurate Ab Initio-Based Potential Energy Curve and Spectroscopic Properties of NO(X2Π) via Extrapolation to the Complete Basis Set Limit (Journal of Atomic and Molecular Sciences, 2017)
The potential energy curves (PECs) of NO (X²Π) have been studied employing a multi-referenceconfiguration interaction method with the Davidson correction and with a series of Dunning'scorrelation-consistent basis sets: aug-c.c.-pvxz(x=T, Q, 5 and 6). Then computed PECs are extrapolated to thecomplete basis set limit. PECs are used to reduce the analytical potential energy functions (APEFs), accurateextended Hartree-Fork methods have been used to investigate electronic structure spectroscopy. Throughthe use of the extended Hartree-Fock approximate correlation energy method to fit APEF, we can calculatethe spectroscopic parameters, consisting with the experimental and theoretical results, and we can also getthe vibrational energy levels, classical turning points, centrifugal distortion constants and inertial rotation.Our calculations are sufficient to close into experimental data from other reference, so the results can supplya useful reference for future experiments.
Keywords: --